PREDICTION OF CARDIOVASCULAR DISEASES WITH THE HELP OF ARTIFICIAL INTELLIGENCE (The New Uzbekistan Journal of Medicine, 2025)
This article explores the potential of artificial intelligence (AI) technologies in the early detection and prediction of cardiovascular diseases. As heart-related conditions remain one of the leading causes of mortality worldwide, timely diagnosis plays a crucial role in preventing severe complications. AI algorithms—particularly those based on machine learning and deep learning—enable the analysis of large volumes of clinical data, uncovering hidden patterns and risk factors with high accuracy. The paper discusses the application of AI in cardiology, including its effectiveness in enhancing diagnostic precision, supporting clinical decision-making, and providing personalized health recommendations. Additionally, the article examines international experiences, key benefits, current limitations, and the future prospects of integrating AI tools into healthcare systems. The findings highlight the growing significance of digital technologies in combating cardiovascular diseases and shaping the future of predictive medicine.